Układ imion w Rdz 49, 3-17. 19-27 i Pwt 33, 6-25 oraz jego znaczenie - Szwarc, Urszula (The Biblical Annals, 2017)
The texts of Gn 49:3-17, 19-27 and Deut 33:6-25 are discussed from a treble point of view: the sequence of births of the sons of Jacob, a chiastic set-up of names in the said pericopes, and conclusions resulting thereof. The text of Genesis attributes equal rank to the house of Judah and Joseph, and Deut places the house of Joseph on top. The so-called "blessings of Jacob" mirror the point of view of all generations as a whole, and the so-called "blessings of Moses", a viewpoint pertaining to the northern generations. The wording of Gn 49 seems then younger than the wording of Deut 33. The position of Judah’s generation in these two texts permits to presume that hagiographers wanted to pinpoint that this generation has an exceptional role to play.